2019
DOI: 10.1038/s41467-019-10226-9
|View full text |Cite
|
Sign up to set email alerts
|

DRP1-mediated mitochondrial shape controls calcium homeostasis and muscle mass

Abstract: Mitochondrial quality control is essential in highly structured cells such as neurons and muscles. In skeletal muscle the mitochondrial fission proteins are reduced in different physiopathological conditions including ageing sarcopenia, cancer cachexia and chemotherapy-induced muscle wasting. However, whether mitochondrial fission is essential for muscle homeostasis is still unclear. Here we show that muscle-specific loss of the pro-fission dynamin related protein (DRP) 1 induces muscle wasting and weakness. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
316
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(359 citation statements)
references
References 61 publications
20
316
4
Order By: Relevance
“…These studies suggest that PRKAR1A deficiency diminished cardiomyocyte hypertrophy in vitro, likely through inactivation of Drp1. It has been shown that loss of Drp1 activity suppresses cardiac hypertrophy and reduces skeletal muscle mass in vivo (Favaro et al, 2019; Hasan et al, 2018). Although phospho‐Drp1 (S637) was undetectable in the heart at 3 months of age (data not shown), it cannot be excluded that ablation of PRKAR1A might enhance Drp1 S637 phosphorylation during early cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that PRKAR1A deficiency diminished cardiomyocyte hypertrophy in vitro, likely through inactivation of Drp1. It has been shown that loss of Drp1 activity suppresses cardiac hypertrophy and reduces skeletal muscle mass in vivo (Favaro et al, 2019; Hasan et al, 2018). Although phospho‐Drp1 (S637) was undetectable in the heart at 3 months of age (data not shown), it cannot be excluded that ablation of PRKAR1A might enhance Drp1 S637 phosphorylation during early cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium and ROS signaling are always crosstalk within mitochondrial microdomains, and mitochondrial calcium is a stimulator of mitochondrial superoxide production in cardiomyocytes. 40 However, the Mfn2-dependent mitochondrial-SR interfaces do not change, indicating that inter-organelle tethering by Mfn2 expression or Drp1 deletion was not perturbed in hearts. Moreover, the intramitochondrial calcium waves or/and superoxide can also stimulate mPTP opening.…”
Section: Discussionmentioning
confidence: 95%
“…Not many studies have addressed how Drp1 modulation affects the mitochondrial Ca 2+ buffering capacity. Drp1 deficiency in myofibers (Favaro et al, 2019) and macrophages (Wang et al, 2017) increases mitCa 2+ levels. Here we observe the opposite effect, suggesting that the role of Drp1 on mitCa 2+ regulation may be context dependent.…”
Section: Resultsmentioning
confidence: 99%